DETEKSI DAN IDENTIFIKASI JAMUR PATOGEN TERBAWA BENIH VARIETAS PADI LOKAL DI KABUPATEN KAPUAS: (Detection and Identification of seedborne pathogenic fungi in Local Rice Varieties in Kapuas Regency) - Mulyani, Rahmawati Budi; Surawijaya, Panji; Hairani, M; Djaya, Adrianson Agus; Pandriyani, Pandriyani (AgriPeat, 2023)
This study was aimed to detect and identify seed-borne pathogenic fungi in six local rice varieties of Siam Unus, Karangdukuh, Mayang, Gumpal Kuning, Gumpal Putih, and Siam Arjuna in Kapuas Regency. In addition, the objective of this study was also to determine the effect of seed pathogens on the physiological quality and the percentage of infected seeds. The research location was at the Agricultural Cultivation Laboratory, Faculty of Agriculture, University of Palangka Raya, and the study was carried out from September 2020 to February 2021. Seed health testing used the filter method (blotter test), isolation and identification of seed-borne pathogenic fungi using the agar method. The variables observed included macroscopic morphology of pathogens in petri dishes and microscopic evaluation using a compound microscope, seed germination, percentage of infected seeds, frequency of microorganism findings and pathogenicity tests on seed germination. Based on the results of the study, the identified pathogenic fungi carried by local varieties of rice seeds in Kapuas district were Aspergillus spp., A. flavus, A. niger, Curvularia sp. and Oidium sp., however these pathogens did not affect seed germination. The highest numbers of microorganisms observed on the agar method was Aspergillus spp. (37.5%), followed by Curvularia sp. (29%), whereas in the blotter test method the frequency of the fungus Curvularia sp. only 5.6%. The frequency of finding A. flavus and A. niger on the agar method was lower at 21.8%, while the fungus Oidium sp. was detected in very low percentage for only 0.9%. The pathogenic fungus Oidium sp. showed the highest level of pathogenicity in seeds reaching 21.7%, while the pathogenic A. niger, Curvularia sp. and A. flavus showed a lower infection rate, at 13.9% to 17.8% respectively. These pathogenic fungi might cause the seeds to not germinate normally such as leading to necrosis of the hypocotyl and plumules, stunted germination growth, and death of seed germination. Keywords: Detection, identification, seed-borne pathogens, local rice varieties, Kapuas